Adenocarcinoma arising in a mucinous cystadenoma of the lung. Issue 2 (February 1992) - Davison, A M; Lowe, J W; Da Costa, P
Abstract : A peripheral nodule in the lung of a 69 year old woman was found on histological examination to contain a focus of adenocarcinoma arising in a mucinous cystadenoma.